Limited asset market participation, sticky wages and monetary policy - Ascari, G; Colciago, A; Rossi, L (Wiley, 2016)
A small amount of nominal wage stickiness makes Limited Asset Market Participation (LAMP) irrelevant for the design of monetary policy. Recent research argues that LAMP could invert the slope of the IS curve in otherwise standard New Keynesian models. This, in turn, implies that optimal monetary policy rules should be passive. We show that the so called Inverted Aggregate Demand Logic (IADL) relies on nominal wage áexibility. Outside of extreme parameterizations, wage stickiness prevents the inversion of the slope of the IS curve. Hence, LAMP does not generally alter the trade-o§s faced by a welfare maximizing Central Bank, and for this reason it does not fundamentally a§ect the design of optimal simple rules and optimal monetary policy.